1998
DOI: 10.1038/sj.onc.1202182
|View full text |Cite
|
Sign up to set email alerts
|

From Src Homology domains to other signaling modules: proposal of the `protein recognition code'

Abstract: The study of oncogenes has illuminated many aspects of cellular signaling. The delineation and characterization of protein modules exempli®ed by Src Homology domains has revolutionized our understanding of the molecular events underlying signal transduction pathways. Several well characterized intracellular modules which mediate protein-protein interactions, namely SH2, SH3, PH, PTB, EH, PDZ, EVH1 and WW domains, are directly involved in the multitude of membrane, cytoplasmic and nuclear processes in multicell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
168
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(168 citation statements)
references
References 37 publications
0
168
0
Order By: Relevance
“…The primary function of RTK tyrosine phosphorylation is to generate binding sites for cytoplasmic or plasma membrane associated proteins involved in transducing proliferative or di erentiating signals to the nucleus. These`signaling proteins' each contain modular Src homology 2 (SH2) (Sadowski et al, 1986) or protein tyrosine binding/ interacting (PTB/PID) (van der Geer et al, 1995) domains and directly interact with phosphotyrosyl proteins in a sequence speci®c manner (reviewed in Pawson and Scott, 1997;Sudol 1998). Such signaling proteins can be loosely grouped into two classes: enzymes and non-enzymatic`adapter' proteins.…”
Section: Erbb-2 Plays a Causal Role In Mammary Tumorigenesismentioning
confidence: 99%
“…The primary function of RTK tyrosine phosphorylation is to generate binding sites for cytoplasmic or plasma membrane associated proteins involved in transducing proliferative or di erentiating signals to the nucleus. These`signaling proteins' each contain modular Src homology 2 (SH2) (Sadowski et al, 1986) or protein tyrosine binding/ interacting (PTB/PID) (van der Geer et al, 1995) domains and directly interact with phosphotyrosyl proteins in a sequence speci®c manner (reviewed in Pawson and Scott, 1997;Sudol 1998). Such signaling proteins can be loosely grouped into two classes: enzymes and non-enzymatic`adapter' proteins.…”
Section: Erbb-2 Plays a Causal Role In Mammary Tumorigenesismentioning
confidence: 99%
“…This concept emerged from the discovery that most protein components of these pathways contain discrete and modular protein-protein interaction domains (Sudol, 1998;Pawson, 2004). These domains have so far been characterized mainly for soluble cytoplasmic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that RSK1 is a dual kinase with independent serine/threonine and tyrosine kinase activities. It is also possible that the phosphorylated tyrosine residues in RSK1 might provide docking sites for phosphotyrosine-binding proteins, such as SH2-or PTB-containing proteins (Sudol, 1998;Margolis et al, 1999) that control distinct KGF-mediated functions.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that RSK family proteins have the potential to associate with the KGFR. Because RSK proteins do not contain SH2 or phosphotyrosine-binding domain (PTB) domains, the typical structural motifs that mediate association with receptor tyrosine kinases (RTKs; Sudol, 1998;Margolis et al, 1999), it is possible that the association between the KGFR and RSK involves an adaptor protein or represents an unconventional interaction with a RTK. Indeed, some RTK-interacting proteins have been identified that do not interact via the conventional phosphotyrosine-SH2/PTB-type interactions.…”
mentioning
confidence: 99%